Wild blue : taming a big-kid bike - Slater, Dashka (Candlewick Press, 2023)
"Kayla loves riding her pink pony, a three-wheeled bike, up and down the street, day after day. But then Daddy announces that it's time for a big-kid bike, one with just two wheels. At the store, Kayla selects her mount, but when she tries to ride it, she is thrown--again and again. Can she tame this intimidating set of wheels? Or is the new blue bike just too wild? Tender and relatable, Wild Blue captures the emotions of moving up in the world through an endearing character with a boundless imagination. Despite falls, bumps, and bruises, Kayla takes her time learning the ropes, until she finally has the confidence to let go of her fear, climb back on, and ride again. Her story will delight and reassure readers transitioning from trikes or training wheels and inspire them to manage setbacks with patience and creativity."--